Cellulose and Chitosan Composite Membranes for Protein and Salt Filtration - Rakbamrung, P.; Wanichapichart, P.; Tirawanichakul, Y. (Journal of Applied Membrane Science & Technology, 2017)
Cellulose membrane (SE) was prepared by culturing Acetobacter xylinum in a media with sucrose as a carbon source and was used as a supporting membrane in this study. Pore size of the supporting membrane was studied by means of molecular weight cut off (MWCO) and SEM micrographs. For making cellulose/chitosan composite membrane SE/CH, chitosan solution was used as a coating polymer and applied by a casting method.This resulted in a smaller hydraulic permeability coefficient (Lp) from 6.7 × 10–11 m3 N–1 s–1 in membrane SE to 1.94 × 10–12 m3 N–1 s–1 in the composite membrane SE/CH. Using PEG of several molecular weights as feed solution, the MWCO of the SE membrane was 200 kDa while that of the SE/CH membrane was 6 kDa. The former rejected 1 g L–1 BSA by 80%. With pH between 3 and 8, the composite membrane SE/CH rejected NaCl and NaHCO3 by 50%, independent of the pH level. However, when using a divalent salt solution of MgSO4 the rejection was increased up to 85%, with an optimum at pH 6–7 and a permeate flux of 5.0 L m–2h–1 at pressures of 0.5 MPa.